No Gangs – Gangs No: Jugend, Subkulturen und Gewalt. Eine Berliner Skizze - Jähner, Uli (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
During the last two decades growing social tensions had a large impact on youth culture. The spreaded notion of gangs shows increasing gangfascination but in contrast to US american cities in Berlin youth violence is not embedded in the patterns of a criminal economy. The distribution of juvenile delinquents and juvenile violence in town is analysed and a new social pathology of violence, which is transgressing the rivaling subcultures, is sketched: bluring the difference between earnest and game.